Aprendiendo a ser mujeres: las escuelas de niñas en la España del siglo XIX - Sarasúa, Carmen (Cuadernos de Historia Contemporánea, 2002)
Occupational segregation between men and women, a central feature of 19th labour markets, was partially due to the characteristics of the workers themselves, whose abilities, qualifications and preferences were heavily genderized. The fact that the ‘shaping’ of the workers took place in childhood explains the interest of studying segregation in schooling. The low rate of female literacy in 19th century Spain has been explained by the low rate of female school attendance. But the deep segregation of the contents of education account as well for this low literacy: girls were schooled within a model that defined sewing, knitting, lace-making and embrodery as the more adequate occupations for women. Thus, girls’ schooling years were mostly devoted to them. Childhood, the age in which we learn, was precisely for this, the age at which girls and boys had to learn which occupations would define them, once adults, as men or women.